Update on the Confederacy of European Patent Information User Groups (CEPIUG). (June 2015) - Baudour, Frederic; Gundertofte, Klaus; Moradei, Guido; Stembridge, Bob; Wretblad, Linus
Abstract: The Confederacy of European Patent Information User Groups (CEPIUG) was founded in 2008 to promote the sharing of experiences and expertise in patent searching across Europe. CEPIUG currently comprises patent information user groups from eight different European countries and is open to new members. Besides the exchange of information, CEPIUG also seeks to promote the coordination of European efforts in the fields of education and training of new entrants into the profession of patent searching, as well as seeking to establish a suitable certification scheme for patent information professionals.